Interfaces entre a gestão social e a educação: estudo de caso no centro popular de cultura e desenvolvimento - CPCD - Parreira, Ludmila Cândido Antunes (2014)
This paper analyzes the social management and some of the effects of this type of management in the People's Center for Culture and Development (CPCD in Brazilian Terms), a non -profit organization, located in the state of Minas Gerais, Brazil. Initially, the social management was investigated to understand the context in which it appears from reading articles, dissertations and documents related to the object of study. Aiming to expand the knowledge of social management, was systematized some of the main ideas and reflections in this field of knowledge from five authors: Fernando Tenório, Paula Schommer, Genauto França Filho, Rosana Boullosa and Edgilson Tavares de Araújo. Besides the social management were worked two other themes: strategic management and the education, to explain, respectively, planning and educational planning. Data from the CPCD were listed from materials and information of their website, plus some work previously carried out of the same organization. To achieve the proposed objectives were also conducted some interviews, semi-structured, with members from various areas of the organization. Finally, were analyzed pivotally, social management, strategic management and education in the nonprofit organization, and arrived at the following results: social management is a field still under construction and, despite efforts of some institutions researching the topic, it is important to insert it into the curriculum of courses such as Administration, so that students understand it as an alternative within the field of management. Moreover, social management and education defended by Paulo Freire, among others, may be related from elements defended on both topics, such as dialogue, participation, autonomy and respect to the knowledge of social actors. Regarding the nonprofit organization, we highlight the limitations of financial resources and partnerships to continue and expand the work that is being done. In addition, it was noted that the social management is present in various aspects of the institution